Direct recanalization of pancreaticogastrostomy obstruction with a forward‐viewing echoendoscope. Issue 1 (14th November 2018) - Kuwatani, Masaki; Kato, Shin; Sakamoto, Naoya
Abstract : Watch a video of this article